Psychopathic traits and deviant sexual interests : the moderating role of gender - Bogaerts, Stefan (2018)
The present study examined associations between psychopathic traits and deviant sexual interests across gender in a large community sample (N = 429, 24% men). Correlation analyses supported the positive link between psychopathic traits and deviant sexual interests. Regression analyses indicated that the unique variance in the antisocial facet of psychopathy predicted all six deviant sexual interests. The interpersonal facet predicted voyeuristic and exhibitionistic interests, whereas the affective facet predicted pedophilic interests. Moderation analyses revealed that gender moderated most of the relations between the antisocial facet of psychopathy and deviant sexual interests, such that those positive associations were stronger among women. On the contrary, the associations between the interpersonal facet and voyeuristic interests, as well as between the lifestyle facet and sadistic interests, were stronger among men. Findings appear to suggest that deviant sexual interests represent a domain in which the manifestation of psychopathic traits may differ across gender. These findings emphasize the relevance of psychopathic traits for the understanding and risk assessment of sexual deviance, while suggesting the need for gender-sensitive considerations